Enhancing MSME Strategic Management in Digital Disruption: Lessons from Thailand and Aceh, Indonesia - Faisal Faisal; Muhammad Adam; Iskandarsyah Madjid; Said Musnadi; Mizan Saddaq (Journal of Community Service and Society Empowerment, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a central role in the economies of Thailand and Indonesia, yet they face increasing pressure from digital disruption and generational shifts. This community service activity aimed to strengthen strategic management awareness through an international knowledge-sharing session conducted at a faculty of management sciences in Southern Thailand on November 5, 2025. The activity employed a classical lecture method combined with interactive discussion, focusing on digital transformation, data-driven strategy, platform competition, and generational adaptation in MSME management. Participants included lecturers and students from both countries, enabling comparative dialogue on regional MSME ecosystems. The findings indicate that participants gained enhanced understanding of digital strategy as a strategic necessity rather than an operational tool. The discussion revealed differences in digital ecosystem maturity between Thailand and Aceh, Indonesia, while also identifying shared structural challenges. The activity underscores the role of academic collaboration in translating research-based strategic concepts into context-sensitive insights and fostering future cooperation for MSME capacity strengthening within the ASEAN region.